Overview of Physical Activity and Cerebrovascular Accident (CVA) Incidence at Blambangan Banyuwangi Regional Hospital for the Period April – May 2025 - Firmanti, Tria Anisa; Alfurqon, Kharisma Choirunisa; Putri, Novita Surya; Sholihin, Sholihin (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Cerebrovascular Accident (CVA) is the second highest mortality rate after heart disease, with the main cause being physical activity. Recurrence of CVA is influenced by physical activity; independence in carrying out physical activity can prevent recurrence and restore function. The purpose of this study was to determine the description of physical activity and the incidence of CVA at Blambangan Banyuwangi Regional Hospital from April to May 2025. This research uses descriptive quantitative observational methods with a case series design of 26 respondents using purposive sampling techniques and the International Physical Activity Questionnaire (IPAQ) questionnaire. The results of this study showed that almost half of the respondents did low physical activity, 42.3%, and the incidence of CVA was mostly CVA infarction, 73.1%. Factors that influence the incidence of CVA include age, gender, and physical activity. The older the age, the risk of CVA increases, with the most cases occurring in males gender and those who have low physical activity, so that they are at high risk of CVA infarction.